Local impact analysis for deck slabs of prestressed concrete box-girder bridges subject to vehicle loading. (January 2017) - Yu, Yang; Deng, Lu; Wang, Wei; Cai, CS
In bridge design codes, the dynamic impact factor (IM) is a well-accepted measure of the impact effect of vehicular loads on bridges. Many previous studies focused on the evaluation of IMs based on the global responses of the main girders while little attention was paid to the local impact effect on bridge decks. As a result, the IMs specified in many design codes, which were traditionally derived from the global responses of bridges, may not be necessarily reasonable for the design of deck slabs. This study was intended to investigate the local impact effect of vehicular loads on the deck slabs of prestressed concrete box-girder bridges. A bridge-vehicle coupled model was adopted to calculate both the local and global IMs. The obtained local and global IMs were compared and the relationship between the IM and three important parameters, including the road surface condition, vehicle speed, and bridge span length, was studied. The results showed that there was no strong correlation between the global and local IMs; however, the local IMs were well correlated with the road surface condition and bridge span length. A discussion on the impact provisions in different bridge codes was also presented.